PRODUCTION, CONSUMPTION AND PRICE (IMPORTS, PRODUCERS AND CONSUMER) VOLATILITY OF SHALLOT IN PROBOLINGGO REGENCY - Susanti Evie Sulistiowati; Ratya Anindita; Rosihan Asmara (Socio-Economics/Agribusiness Department, 2021)
Changes in production, consumption, and import variables cause the price of shallots to fluctuate. A high and unpredictable price fluctuation increasing the volatility problem. This phenomenon gives results in risk, uncertainty and leading to a decline in the welfare of producers and consumers. Based on the description of the problems above, it is important to analyze price, production, import, and consumption volatility to determined the level of risk and uncertainty faced by producers and consumers. This study uses monthly secondary data (time series) on production, price, imports, and consumption of shallots in Probolinggo Regency, for seven years (2013-2019). The ARCH/GARCH method is used to analyze the volatility of prices, production and consumption. The results from the analysis are the production variable has a low level of volatility, the consumption and import prices have high-level volatility, producer price has low-level volatility, while consumer prices has-high level volatility. From the results means that the risks and uncertainties faced by producers in conducting shallot cultivation are low. While for the consumer means the risks and uncertainties in consuming shallots are high.